Na V1.8, but not Na V1.9, is upregulated in the inflamed dental pulp tissue of human primary teeth - A. Suwanchai (2018)
Aim To investigate alterations in Na V1.8 and Na V1.9 expression within inflamed dental pulp tissue of human primary teeth. Methodology Dental pulp tissue obtained from both normal and inflamed pulps in primary teeth as well as pulps from normal and inflamed permanent teeth was used. The quantity of Na V1.8 and Na V1.9 expression in the dental pulp tissue was investigated using Western blot analysis. General neuron marker (PGP9.5) was used to quantify for neural density, and an increase in metalloproteinase-9 was used to indicate pulpal inflammation in inflamed teeth. Statistically significant differences for each determined parameter between normal and inflamed teeth of both primary and permanent teeth were tested using the Mann-Whitney rank sum test. Results There was no significant difference in neural density of normal and inflamed dental pulp tissue, although degrees of inflammation were increased in the inflamed dental pulp of both permanent and primary teeth (P<0.05). Na V1.8 and Na V1.9 expression in inflamed pulps of permanent teeth increased significantly compared with normal permanent teeth (P<0.05). However, only Na V1.8 expression was increased significantly in the inflamed dental pulp of primary teeth (P<0.05). Conclusions Na V1.8 alone may be the therapeutic target for treatment of painful pulpitis in primary teeth. © 2011 International Endodontic Journal.